Nonaqueous electrolyte secondary battery

By using a spacer with a heat-resistant layer and a convex portion of the resin particle in a nonaqueous electrolyte secondary battery, the problem of deformation of the electrode plate during the charge and discharge cycle is solved, and the stability and life of the battery are improved.

CN119487692APending Publication Date: 2025-02-18PANASONIC ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380054183.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-27
Filing Date
2023-07-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In a nonaqueous electrolyte secondary battery, the electrode body will expand during the charge and discharge cycle, causing the outer packaging body to apply pressure to the electrode body, causing the plate to bend and deform, and increasing the risk of internal short circuit.

Method used

A spacer with a base material layer and a functional layer is used, and the functional layer includes a heat-resistant layer containing a heat-resistant resin and inorganic particles, and resin particles dispersed in the heat-resistant layer, and the resin particles form convex protruding from the surface of the heat-resistant layer. to improve the adhesion between the electrode and the spacer and to suppress deformation of the electrode plate.

Benefits of technology

It effectively suppresses the deformation of the electrode plate during the charge and discharge cycle, reduces the risk of internal short circuits, and improves the stability and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487692A_ABST
    Figure CN119487692A_ABST
Patent Text Reader

Abstract

The non-aqueous electrolyte secondary battery has an electrode body in which a positive electrode and a negative electrode are wound with a separator (13) interposed therebetween, and an exterior body that accommodates the electrode body, and the separator (13) has a base material layer (30) and a functional layer (32) formed on the base material layer (30). The functional layer (32) includes a heat-resistant layer (34) containing a heat-resistant resin and inorganic particles, and resin particles (36) dispersed in the heat-resistant layer (34) and having an average particle diameter larger than the thickness of the heat-resistant layer (34). The resin particles (36) form protrusions (36a) protruding from the surface of the heat-resistant layer (34).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-aqueous electrolyte secondary battery. Background Art

[0002] In recent years, nonaqueous electrolyte secondary batteries including an electrode body in which a positive electrode and a negative electrode are arranged to face each other with a separator interposed therebetween have been widely used as secondary batteries with high output and high energy density.

[0003] For example, Patent Document 1 discloses a technique for setting the static friction coefficient of the surface of a separator to 0.45 or less in order to improve the pulling-out property of a winding core when manufacturing a wound electrode assembly.

[0004] For example, Patent Document 2 discloses a separator including a substrate and a layer containing a heat-resistant resin and inorganic particles formed on the substrate.

[0005] For example, Patent Document 3 discloses a separator including a substrate and a functional layer including inorganic particles and resin particles formed on the substrate, wherein the volume average particle size of the resin particles is larger than the thickness of the inorganic particle layer including the inorganic particles.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-126275

[0009] Patent Document 2: Japanese Patent No. 3175730

[0010] Patent Document 3: International Publication No. 2020 / 175079 Summary of the invention

[0011] However, in a non-aqueous electrolyte secondary battery in which a wound electrode body is housed in an outer packaging body, when the electrode body expands with charge and discharge cycles, pressure is applied to the electrode body from the outer packaging body, and the electrode plates constituting the electrode body may be deformed, causing the electrode plates to bend. Since the deformation of the electrode plate can be a cause of internal short circuit, it is an important issue to suppress the deformation of the electrode plate.

[0012] Therefore, an object of the present invention is to provide a non-aqueous electrolyte secondary battery capable of suppressing deformation of an electrode plate accompanying a charge and discharge cycle.

[0013] The non-aqueous electrolyte secondary battery of the present invention is characterized in that it comprises an electrode body formed by winding a positive electrode and a negative electrode with a separator sandwiched therebetween, and an outer packaging body accommodating the above-mentioned electrode body, the above-mentioned separator has a substrate layer and a functional layer formed on the above-mentioned substrate layer, the above-mentioned functional layer includes a heat-resistant layer containing a heat-resistant resin and inorganic particles, and resin particles dispersed in the above-mentioned heat-resistant layer and having an average particle size greater than the thickness of the above-mentioned heat-resistant layer, and the above-mentioned resin particles form a convex portion protruding from the surface of the above-mentioned heat-resistant layer.

[0014] According to the present invention, a non-aqueous electrolyte secondary battery can be provided which can suppress deformation of the electrode plate accompanying the charge and discharge cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0016] Figure 2 It is a schematic cross-sectional view showing an example of the spacer according to the present embodiment.

[0017] Figure 3 It is a diagram for explaining the evaluation method of electrode plate deformation. DETAILED DESCRIPTION

[0018] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present invention will be described in detail.

[0019] Figure 1 It is a schematic cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment. Figure 1 The non-aqueous electrolyte secondary battery 10 shown includes a wound electrode body 14 in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween, a non-aqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode body 14, and a battery case 15. The battery case 15 includes: an outer package 16 that accommodates the electrode body 14, the non-aqueous electrolyte, etc.; and a sealing body 17 that seals the opening of the outer package 16. The battery case 15 is not limited to a cylindrical or square metal case, and may be, for example, a resin case formed by laminating resin sheets (so-called laminated type) or the like.

[0020] The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may also contain a halogen substitute in which at least a portion of the hydrogen of these solvents is replaced by a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6. It should be noted that the non-aqueous electrolyte is not limited to a liquid electrolyte, and may also be a solid electrolyte such as a gel polymer.

[0021] The outer package 16 is, for example, a metal container in a cylindrical shape with a bottom. A gasket 28 is provided between the outer package 16 and the sealing body 17 to ensure the airtightness of the battery interior. The outer package 16 has, for example, a protrusion 22 for supporting the sealing body 17, which is obtained by protruding a part of the side surface inward. The protrusion 22 is preferably formed in an annular shape along the circumferential direction of the outer package 16, and the sealing body 17 is supported by its upper surface.

[0022] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cap 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the non-aqueous electrolyte secondary battery 10 rises due to heat caused by an internal short circuit, for example, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cap 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.

[0023] Figure 1 In the non-aqueous electrolyte secondary battery 10 shown, the positive electrode lead 20 attached to the positive electrode 11 passes through the through hole of the insulating plate 18 and extends to the sealing body 17 side, and the negative electrode lead 21 attached to the negative electrode 12 passes through the outside of the insulating plate 19 and extends to the bottom side of the outer package 16. The positive electrode lead 20 is connected to the lower surface of the filter 23 as the bottom plate of the sealing body 17 by welding or the like, and the cap 27 as the top plate of the sealing body 17 electrically connected to the filter 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer package 16 by welding or the like, and the outer package 16 serves as the negative terminal.

[0024] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 will be described.

[0025] [positive electrode]

[0026] The positive electrode 11 has a positive electrode collector and a positive electrode mixture layer formed on the surface of the positive electrode collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode collector. The positive electrode collector can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a film having the metal configured on the surface, etc. The positive electrode mixture layer, for example, includes a positive electrode active material, a binder, a conductive agent, etc. For example, a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent, etc. is applied to the positive electrode collector, and after the coating is dried, it is rolled to form a positive electrode mixture layer on both sides of the positive electrode collector, thereby making the positive electrode 11.

[0027] Examples of the positive electrode active material contained in the positive electrode mixture layer include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. For example, lithium transition metal oxides are Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). They can be used alone or in combination. From the perspective of achieving a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO2、Li x Co y Ni 1-y O2、Li x Ni 1-y M y O z (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3) etc. Inorganic particles such as tungsten oxide, aluminum oxide, and compounds containing lanthanide elements can be firmly attached to the surface of the lithium transition metal oxide particles.

[0028] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon materials, etc. These may be used alone or in combination of two or more.

[0029] As the binder contained in the positive electrode mixture layer, fluorine resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, etc. can be exemplified. They can be used alone or in combination of two or more. In addition, these resins can also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0030] [negative electrode]

[0031] The negative electrode 12 has a negative electrode collector and a negative electrode mixture layer formed on the surface of the negative electrode collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode collector. The negative electrode collector can use a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode, a film having the metal configured on the surface, etc. The negative electrode mixture layer, for example, contains a negative electrode active material, a binder, etc. For example, a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. is applied to the negative electrode collector, and after the coating is dried, it is rolled to form a negative electrode mixture layer on both sides of the negative electrode collector, thereby making the negative electrode 12.

[0032] The negative electrode active material contained in the negative electrode mixture layer is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and carbon-based active materials such as graphite are generally used. Graphite can be any of natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite, and artificial graphites such as graphitized mesophase carbon microbeads. In addition, as the negative electrode active material, metals such as Si and Sn alloyed with Li, metal compounds containing Si, Sn, etc., lithium-titanium composite oxides, etc. can also be used. As negative electrode active materials other than carbon-based active materials, silicon-based active materials are preferred. As silicon-based active materials, for example, SiO x (0.5≤x≤1.6) Si-containing compounds, or Li 2y SiO (2+y) The Si-containing compound represented by (0<y<2) is a compound in which Si particles are dispersed in a lithium silicate phase. The content of the silicon-based active material in the negative electrode mixture layer is, for example, preferably 1 mass % to 15 mass %, more preferably 5 mass % to 10 mass % relative to the total mass of the negative electrode active material.

[0033] It is preferred that a conductive film is formed on the particle surface of the silicon-based active material. As the constituent material of the conductive film, at least one selected from carbon materials, metals and metal compounds can be exemplified. Among them, carbon materials such as amorphous carbon are preferred. The carbon film can be formed, for example, by a CVD method using acetylene, methane, etc., a method of mixing coal tar, petroleum asphalt, phenolic resin, etc. with silicon-based active material particles and heat treating them. In addition, a conductive film can also be formed by firmly attaching a conductive filler such as carbon black to the particle surface of the silicon-based active material using a binder.

[0034] The binder contained in the negative electrode mixture layer can be PTFE, PVDF and other fluorine-containing resins, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode, but preferably styrene-butadiene rubber (SBR). In addition, the negative electrode mixture layer can contain CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc.

[0035] [Spacer]

[0036] Figure 2 Schematic cross-sectional view showing an example of a spacer according to the present embodiment. Figure 2 As shown, the spacer 13 includes a substrate 30 and a functional layer 32 formed on the substrate 30. The functional layer 32 may be provided on one surface of the substrate 30 or on both surfaces of the substrate 30.

[0037] The substrate 30 is, for example, a porous sheet having ion permeability and insulation, and specifically, may be a microporous film, woven fabric, nonwoven fabric, etc. The material of the substrate 30 is not particularly limited, and may be, for example, polyethylene, polypropylene, polyolefins such as copolymers of polyethylene and α-olefins, acrylic resins, polystyrene, polyester, cellulose, polyimide, polyphenylene sulfide, polyetheretherketone, fluororesins, etc.

[0038] The functional layer 32 includes a heat-resistant layer 34 containing a heat-resistant resin and inorganic particles, and resin particles 36 dispersed in the heat-resistant layer 34 and having an average particle size (D50) larger than the thickness of the heat-resistant layer 34. The resin particles 36 having an average particle size (D50) larger than the thickness of the heat-resistant layer 34 form convex portions 36a protruding from the surface of the heat-resistant layer 34.

[0039] It is believed that, by the above-mentioned structure, the convex portion 36a composed of the resin particles 36 is bonded to the electrode (positive electrode 11, negative electrode 12) opposite to the separator 13, and the adhesion between the separator 13 and the electrode is improved, so that the deformation of the electrode accompanying the charge and discharge cycle can be suppressed. In the case where the functional layer 32 is provided on one side of the substrate 30, the separator 13 can be provided between the positive electrode 11 and the negative electrode 12 in such a manner that the functional layer 32 is opposite to the positive electrode 11, or the separator 13 can be provided between the positive electrode 11 and the negative electrode 12 in such a manner that the functional layer 32 is opposite to the negative electrode 12. However, since it is believed that it is important to suppress the deformation of the positive electrode 11 in order to effectively suppress the internal short circuit caused by the deformation of the electrode plate, it is preferred that the separator 13 is provided between the positive electrode 11 and the negative electrode 12 in such a manner that the functional layer 32 is opposite to the positive electrode 11, so that the convex portion 36a is bonded to the positive electrode 11.

[0040] Examples of the inorganic particles contained in the heat-resistant layer 34 include metal oxide particles, metal nitride particles, metal fluoride particles, and metal carbide particles.

[0041] Examples of metal oxide particles include aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, nickel oxide, silicon oxide, and manganese oxide. Examples of metal nitride particles include titanium nitride, boron nitride, aluminum nitride, magnesium nitride, and silicon nitride. Examples of metal fluoride particles include aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, and barium fluoride. Examples of metal carbide particles include silicon carbide, boron carbide, titanium carbide, and tungsten carbide.

[0042] The inorganic particles may also be zeolite (M 2 / n O·Al2O3·xSiO2·yH2O, M is a metal element, n is the valence of M, x≥2, y≥0) and other porous aluminosilicates, talc (Mg3Si4O 10 (OH)2) and other layered silicates, barium titanate (BaTiO3), strontium titanate (SrTiO3) and other minerals, etc. It should be noted that these may be used alone or in combination of two or more.

[0043] The average particle size (D50) of the inorganic particles is preferably in the range of 0.1 μm to 1.0 μm, for example. In this specification, D50 means the particle size at which the cumulative frequency in the volume-based particle size distribution reaches 50% from the smaller particle size, also known as the median diameter. The particle size distribution of the inorganic particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac Bel Co., Ltd.) using water as a dispersion medium.

[0044] The content of the inorganic particles contained in the heat-resistant layer 34 is, for example, preferably in the range of 15 mass % to 85 mass %, and more preferably in the range of 30 mass % to 60 mass %, relative to the total mass of the heat-resistant layer 34 .

[0045] As the heat-resistant resin contained in the heat-resistant layer 34, for example, it is preferred to use a resin that does not melt or decompose in a temperature range below 200°C. Specifically, from the perspective of high heat resistance, nitrogen-containing aromatic polymers and the like can be cited. The so-called nitrogen-containing aromatic polymer is a polymer containing nitrogen atoms and aromatic rings in the main chain, and examples thereof include aromatic polyamides (hereinafter sometimes referred to as "aromatic polyamides"), aromatic polyimides (hereinafter sometimes referred to as "polyimides"), and aromatic polyamide-imides (hereinafter sometimes referred to as "polyamide-imides"), etc. As aromatic polyamides, for example, meta-oriented aromatic polyamides (hereinafter sometimes referred to as "meta-aromatic polyamides") and para-oriented aromatic polyamides (hereinafter sometimes referred to as "para-aromatic polyamides") can be cited. They can be used alone or in combination of two or more.

[0046] The content of the heat-resistant resin is preferably 15 to 85% by mass, and more preferably 40 to 70% by mass, based on the total mass of the heat-resistant layer 34 , for example, in order to improve the heat resistance of the separator 13 .

[0047] The thickness of the heat-resistant layer 34 is preferably smaller than the thickness of the base material 30 , and is, for example, 0.5 μm to 5 μm.

[0048] The heat-resistant layer 34 preferably further includes a binder. The binder has the function of bonding the individual inorganic particles to each other and bonding the inorganic particles to the substrate 30. As an example of a binder, fluorine-based resins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide-based resins, acrylic resins, polyolefin-based resins, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyvinyl alcohol (PVA), etc. can be cited. They can be used alone or in combination of two or more. The content of the binder contained in the heat-resistant layer 34 is preferably 0.5 to 10% by mass, and more preferably 1 to 5% by mass, relative to the total mass of the heat-resistant layer 34.

[0049] The resin particles 36 dispersed in the heat-resistant layer 34 need to have an average particle size (D50) larger than the thickness of the heat-resistant layer 34. The average particle size (D50) of the resin particles 36 is preferably 1 μm to 10 μm larger than the thickness of the heat-resistant layer 34. If the average particle size (D50) of the resin particles 36 is 1 μm or more larger than the thickness of the heat-resistant layer 34, for example, it is easy to form convex portions 36a protruding from the surface of the heat-resistant layer 34, and good adhesion to the electrode can be ensured. In addition, if the average particle size (D50) of the resin particles 36 is 10 μm or less larger than the thickness of the heat-resistant layer 34, it is possible to suppress the resin particles 36 from falling off the heat-resistant layer 34.

[0050] Regarding the content of the resin particles 36 dispersed in the heat-resistant layer 34, for example, from the perspective of ensuring good adhesion to the electrode, the content is preferably in the range of 1 mass % to 15 mass % relative to the mass of the heat-resistant resin contained in the heat-resistant layer 34, and more preferably in the range of 3 mass % to 7 mass %.

[0051] Regarding the protrusions 36a formed by the resin particles 36, for example, from the perspective of ensuring good adhesion with the electrode, when looking down at the surface of the functional layer 32, preferably there are 10 to 35 protrusions 36a in the range of 100 μm×100 μm, and more preferably there are 15 to 30 protrusions 36a.

[0052] As the resin particles 36, for example, a known polymer that can be used as a binder when forming the functional layer 32 can be used. As monomer units constituting the resin particles 36 (polymer), for example, aromatic vinyl monomer units, (meth) acrylic acid ester monomer units, fluorine-containing monomer units, etc. can be cited. It should be noted that in the present invention, the so-called "(meth) acrylic acid" means acrylic acid and / or methacrylic acid. It should be noted that the so-called resin particles 36 (polymer) "containing monomer units" means that the polymer obtained using the monomer contains repeating units derived from the monomer.

[0053] Examples of the aromatic vinyl monomer capable of forming the aromatic vinyl monomer unit are not particularly limited, and examples thereof include styrene, α-methylstyrene, styrenesulfonic acid, butoxystyrene, and vinylnaphthalene. Examples of the (meth)acrylate monomers that can form the (meth)acrylate monomer units include butyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, and tert-butyl acrylate; alkyl acrylates such as octyl acrylates such as pentyl acrylate, hexyl acrylate, heptyl acrylate, and 2-ethylhexyl acrylate; nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and butyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate; octyl methacrylates such as pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, and 2-ethylhexyl methacrylate; nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate; and alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate.

[0054] Examples of the fluorine-containing monomer capable of forming the fluorine-containing monomer unit are not particularly limited, and examples thereof include vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, vinyl fluoride, and perfluoroalkyl vinyl ether.

[0055] The resin particles 36 may further include crosslinking monomer units on the basis of the above-mentioned monomer units. Here, the so-called crosslinking monomer unit is a monomer that can form a crosslinking structure during or after polymerization by heating or irradiation with energy rays. As a monomer that can form a crosslinking monomer unit, for example, a multifunctional monomer having two or more polymerization reactive groups in the monomer can be cited. As such a multifunctional monomer, for example, divinyl compounds such as allyl methacrylate and divinylbenzene can be cited; di(meth)acrylate compounds such as diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and 1,3-butanediol diacrylate; tri(meth)acrylate compounds such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allyl glycidyl ether and glycidyl methacrylate; etc.

[0056] The resin particles 36 can be prepared by polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. The polymerization method is not particularly limited, and may be, for example, a suspension polymerization method, an emulsion polymerization coagulation method, a pulverization method, etc. In addition, as the polymerization reaction, any reaction such as free radical polymerization and living free radical polymerization can be used.

[0057] The monomer composition used to prepare the resin particles 36 may contain other additives such as a chain transfer agent, a polymerization regulator, a polymerization reaction retarder, a reactive fluidizing agent, a filler, a flame retardant, an antioxidant, and a colorant in any amount.

[0058] An example of a method for producing the spacer 13 of the present embodiment is described. For example, inorganic particles, a heat-resistant resin, resin particles 36, water as a dispersion medium, and other components (such as a binder, etc.) used as needed are mixed to prepare a slurry composition for a functional layer. Thereafter, the slurry for a functional layer is applied to a substrate and then dried, thereby producing the spacer 13 of the present embodiment.

[0059] Example

[0060] Hereinafter, the present invention will be further described using examples; however, the present invention is not limited to these examples.

[0061] <Example 1>

[0062] [Production of positive electrode]

[0063] 100 parts by mass of LiNi 0.88 Co 0.09 Al 0.03O2, 1 part by mass of acetylene black (AB) and 0.9 parts by mass of polyvinylidene fluoride (PVDF) were mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode mixture slurry. Then, the positive electrode mixture slurry was applied to both sides of an aluminum foil with a thickness of 15 μm, and the coating was dried. Thereafter, the coating was rolled using a roller, and then cut into a specified electrode size (thickness 0.144 mm, width 62.6 mm, length 861 mm) to produce a positive electrode with a positive electrode mixture layer formed on both sides of the positive electrode collector. In the central part of the longitudinal direction of the positive electrode, an exposed portion where the positive electrode mixture layer is not formed and the positive electrode collector is exposed is provided, and an aluminum positive electrode lead is welded to the exposed portion.

[0064] [Production of negative electrode]

[0065] 95 parts by mass of graphite powder, 5 parts by mass of Si oxide, 1 part by mass of sodium carboxymethylcellulose (CMC-Na) and 1 part by mass of styrene butadiene rubber (SBR) dispersion were mixed, and an appropriate amount of water was added to prepare a negative electrode mixture slurry. Then, the negative electrode mixture slurry was applied to both sides of a copper foil with a thickness of 8 μm, and the coating was dried. Thereafter, the coating was rolled using a roller, and then cut into a specified electrode size to produce a negative electrode with a negative electrode mixture layer formed on both sides of the negative electrode collector. At one end of the negative electrode in the longitudinal direction (the end located on the inner side of the winding of the electrode body), an exposed portion where the negative electrode mixture layer is not formed and the negative electrode collector is exposed is provided, and a nickel negative electrode lead is welded to the exposed portion.

[0066] [Making spacers]

[0067] A porous substrate made of polyethylene with a thickness of 12 μm was prepared. Para-aramid (heat-resistant resin), α-Al2O3 powder (inorganic particles) with an average particle size (D50) of 0.8 μm, acrylic resin particles containing a copolymer of 2-ethylhexyl acrylate and styrene with an average particle size (D50) of 4 μm (hereinafter referred to as acrylic resin particles), and an acrylic adhesive (binder) were mixed at a solid content mass ratio of 100:150:6:5, and an appropriate amount of water was added so that the solid content concentration was 10% by mass to prepare a functional layer slurry. The functional layer slurry was applied to the entire area of ​​one surface of the substrate using a micro gravure coater, and the coating was heated and dried in an oven at 50°C for 4 hours to obtain a spacer having a functional layer with a heat-resistant layer having an average thickness of 3 μm formed on one surface of the substrate.

[0068] The surface of the functional layer of the obtained separator was observed with a scanning electron microscope. As a result, 10 projections protruding from a part of the resin particles of the heat-resistant layer were confirmed within an area of ​​100 μm×100 μm.

[0069] [Electrode body production]

[0070] The positive electrode and the negative electrode were wound in a spiral shape with a separator interposed therebetween to produce a wound electrode body. At this time, the separator was arranged so that the functional layer of the separator faced the positive electrode. The number of windings of the electrode body was set to 18 times based on the positive electrode.

[0071] [Preparation of non-aqueous electrolyte]

[0072] To 100 parts by mass of a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 3:7, 5 parts by mass of vinylene carbonate (VC) was added, and lithium hexafluorophosphate (LiPF6) was dissolved at a concentration of 1.5 mol / L to prepare a non-aqueous electrolyte.

[0073] [Manufacturing of non-aqueous electrolyte secondary batteries]

[0074] Insulating plates were placed above and below the electrode body, and the electrode body was placed in an outer can. The negative electrode lead was welded to the bottom of the outer can with a bottom and the positive electrode lead was welded to the sealing body. After injecting a non-aqueous electrolyte into the outer can, the opening of the outer can was sealed with a sealing body through a gasket, and then left to stand in a constant temperature chamber at 60°C for 15 hours to produce a non-aqueous electrolyte secondary battery.

[0075] [Evaluation of plate deformation]

[0076] The above-mentioned non-aqueous electrolyte secondary battery was charged at a constant current of 0.3It until the battery voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.02It. Thereafter, it was discharged at a constant current of 1.0It until the battery voltage reached 2.7V. A rest period of 20 minutes was inserted between each cycle, and the charge and discharge cycle was performed for 500 cycles. After 500 cycles, the non-aqueous electrolyte secondary battery was charged at a constant current of 0.3It until the battery voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.02It to set it to a charged state. The cross-section of the non-aqueous electrolyte secondary battery in the charged state was observed using an X-ray CT device (manufactured by Shimadzu Corporation, SMX-225CT FPD HR) near the winding center of the electrode body. As shown Figure 3 As shown, when deformation (bending) of the electrode plate (at least one of the positive electrode 11 and the negative electrode 12) was confirmed to be 150 degrees or less, it was determined that the electrode plate was deformed, and the presence or absence of electrode plate deformation was evaluated. The number of batteries evaluated was 3.

[0077] <Example 2>

[0078] A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the production of the separator, para-aramid, α-Al2O3 powder (inorganic particles) with an average particle size (D50) of 0.8 μm, acrylic resin particles with an average particle size (D50) of 4 μm, and acrylic adhesive (binder) were mixed in a solid content mass ratio of 100:150:9:5. The plate deformation was evaluated.

[0079] The surface of the functional layer of the separator of Example 2 was observed with a scanning electron microscope. As a result, 18 protrusions of the resin particles protruding from the heat-resistant layer were confirmed in an area of ​​100 μm×100 μm.

[0080] <Example 3>

[0081] A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the production of the separator, para-aramid, α-Al2O3 powder (inorganic particles) with an average particle size (D50) of 0.8 μm, acrylic resin particles with an average particle size (D50) of 4 μm, and acrylic adhesive (binder) were mixed in a solid content mass ratio of 100:150:18:5. The plate deformation was evaluated.

[0082] The surface of the functional layer of the separator of Example 3 was observed with a scanning electron microscope. As a result, 35 protrusions of the resin particles protruding from the heat-resistant layer were confirmed in an area of ​​100 μm×100 μm.

[0083] <Example 4>

[0084] A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the production of the separator, para-aramid, α-Al2O3 powder (inorganic particles) with an average particle size (D50) of 0.8 μm, acrylic resin particles with an average particle size (D50) of 6 μm, and acrylic adhesive (binder) were mixed in a solid content mass ratio of 100:150:15:5. The plate deformation was evaluated.

[0085] The surface of the functional layer of the separator of Example 4 was observed with a scanning electron microscope. As a result, 25 protrusions of the resin particles protruding from the heat-resistant layer were confirmed in an area of ​​100 μm×100 μm.

[0086] <Example 5>

[0087] A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the production of the separator, para-aramid, α-Al2O3 powder (inorganic particles) with an average particle size (D50) of 0.8 μm, acrylic resin particles with an average particle size (D50) of 10 μm, and acrylic adhesive (binder) were mixed in a solid content mass ratio of 100:150:24:5. The plate deformation was evaluated.

[0088] The surface of the functional layer of the separator of Example 5 was observed with a scanning electron microscope. As a result, 10 protrusions of the resin particles protruding from the heat-resistant layer were confirmed in an area of ​​100 μm×100 μm.

[0089] <Example 6>

[0090] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that meta-aramid was used as the heat-resistant resin in the production of the separator, and the plate deformation was evaluated.

[0091] The surface of the functional layer of the separator of Example 6 was observed with a scanning electron microscope. As a result, 10 protrusions of the resin particles protruding from the heat-resistant layer were confirmed in an area of ​​100 μm×100 μm.

[0092] <Example 7>

[0093] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that polyamide-imide was used as the heat-resistant resin in the production of the separator, and the electrode plate deformation was evaluated.

[0094] The surface of the functional layer of the separator of Example 7 was observed with a scanning electron microscope. As a result, 11 protrusions of the resin particles protruding from the heat-resistant layer were confirmed in an area of ​​100 μm×100 μm.

[0095] <Comparative Example>

[0096] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except that the acrylic resin particles having an average particle size (D50) of 4 μm were not used in the production of the separator, and the electrode plate deformation was evaluated.

[0097] The evaluation results of the electrode plate deformation of Examples 1 to 7 and Comparative Example are summarized in Table 1. When all the three batteries evaluated had no electrode plate deformation, the evaluation was 0, and when electrode plate deformation was confirmed, even if only one battery had electrode plate deformation, the evaluation was ×.

[0098]

[0099] As can be seen from the evaluation results in Table 1, in Examples 1 to 7, no plate deformation occurred, but in the comparative example, plate deformation occurred. By using a separator as in the examples, that is, having a substrate layer and a functional layer formed on the substrate layer, the functional layer comprising a heat-resistant layer containing a heat-resistant resin and inorganic particles, and resin particles dispersed in the heat-resistant layer and having an average particle size greater than the thickness of the heat-resistant layer, the resin particles forming convex portions protruding from the surface of the heat-resistant layer, it is possible to suppress plate deformation caused by charge and discharge cycles.

[0100] [appendix] (1)

[0102] A non-aqueous electrolyte secondary battery comprises an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, and an outer package body for housing the electrode body.

[0103] The spacer comprises a base material layer and a functional layer formed on the base material layer.

[0104] The functional layer includes a heat-resistant layer containing a heat-resistant resin and inorganic particles, and resin particles dispersed in the heat-resistant layer and having an average particle size larger than the thickness of the heat-resistant layer.

[0105] The resin particles form projections protruding from the surface of the heat-resistant layer. (2)

[0107] The nonaqueous electrolyte secondary battery according to (1) above, wherein the average particle diameter of the resin particles is 1 μm to 10 μm larger than the thickness of the heat-resistant layer. (3)

[0109] The nonaqueous electrolyte secondary battery according to (1) or (2), wherein the resin particles have adhesive properties, and the protrusions are bonded to the positive electrode. (4)

[0111] The non-aqueous electrolyte secondary battery according to any one of (1) to (3) above, wherein the heat-resistant resin comprises at least one of para-aramid, meta-aramid, polyamideimide, and polyimide. (5)

[0113] The nonaqueous electrolyte secondary battery according to any one of (1) to (4) above, wherein in a plan view of the surface of the functional layer, 10 to 35 of the protrusions exist within a range of 100 μm×100 μm.

[0114] Description of Reference Numerals

[0115] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 battery case, 16 outer packaging body, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 protrusion, 23 filter, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cap, 28 gasket, 30 substrate, 32 functional layer, 34 heat-resistant layer, 36 resin particles, 36a protrusion.

Claims

1. A non-aqueous electrolyte secondary battery comprising an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, and an outer packaging body for housing the electrode body, The spacer comprises a base material layer and a functional layer formed on the base material layer. The functional layer includes a heat-resistant layer containing a heat-resistant resin and inorganic particles, and resin particles dispersed in the heat-resistant layer and having an average particle size larger than the thickness of the heat-resistant layer. The resin particles form projections protruding from the surface of the heat-resistant layer.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The average particle diameter of the resin particles is 1 μm to 10 μm larger than the thickness of the heat-resistant layer.

3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The protrusion is bonded to the positive electrode.

4. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The heat-resistant resin includes at least any one of para-aramid, meta-aramid, polyamideimide, and polyimide.

5. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: When the surface of the functional layer is viewed in plan, 10 to 35 protrusions exist within a range of 100 μm×100 μm.

Citation Information

Patent Citations

  • Laminated porous film, battery separator, and battery

    JP2011126275A

  • Functional layer for electrochemical elements, separator with functional layer for electrochemical elements, and electrochemical element

    WO2020175079A1